"She's a dog at the end of the day": guide dog owners' perspectives on the behaviour of their guide dog - Craigon, Peter J.; Hobson-West, Pru; England, Gary C.W.; Whelan, Chantelle T.; Lethbridge, Emma; Asher, Lucy (Public Library of Science, 2017)
A guide dog is a domestic dog (Canis familiaris) that is specifically educated to provide mobility support to a blind or visually impaired owner. Current dog suitability assessments focus on behavioural traits, including: trainability, reactivity or attention to environmental stimuli, low aggressiveness, fearfulness and stress behaviour, energy levels, and attachment behaviour. The aim of this study was to find out which aspects of guide dog behaviour are of key importance to guide dog owners themselves. Sixty-three semi-structured interview surveys were carried out with guide dog owners. Topics included the behaviour of their guide dog both within and outside their working role, and also focused on examples of behaviour which might be considered outside a guide dog owner’s typical expectations. Both positive and negative examples and situations were covered. This allowed for the discovery of new perspectives and emerging themes on living and working with a guide dog. Thematic analysis of the results reveals that a dog’s safe behaviour in the face of traffic was the most important positive aspect of a guide dog’s behaviour and pulling or high tension on the lead and /or harness was the most discussed negative aspect. Other aspects of guide dog behaviour were highlighted as particularly pleasing or disappointing by owners including attentiveness to the task, work, environment and owner; confidence in work and decision making (with confident dogs resulting in confident owners) obedience and control; calmness and locating objectives. The results reveal important areas of behaviour that are not currently considered priorities in guide dog assessments; these key areas were consistency of behaviour, the dog’s maturity and the dog’s behaviour in relation to children. The survey revealed a large range in what owners considered problematic or pleasing behaviours and this highlights the heterogeneity in guide dog owners and the potential multifarious roles of the guide dog. This study contributes to the literature on which behaviour is considered appropriate or inappropriate in dogs and on the nature of human-animal interactions.